PEMANFAATAN STEVIA SEBAGAI PEMANIS ALAMI PADA SARI BUAH BELIMBING - DARYANTI DARYANTI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2012)
Except for economic motive, consideration of special consumer demand such as diabetes patients has been increased utilization of sweeteners. But for healthy porposes, the sweetener must be natural, non toxic, low calorie and stable during process. Stevia is a sweetener which have that requirements. In recent year, there are stevia pure derivative products in the market but in high price so has not been used by small industries. Therefore, this study was aim to optimize utilization of stevia through simple extraction to produce sweetener for starfruit juice as small industry product. The research were divided to four step, they were determining of stevia leaves preparation, determining of extraction methode, determining of cold storage effect and determining of appropriate stevia concentration. The result showed that neither pH nor total soluble solid of starfruit juice were change by addition of stevia. According to organoleptic test we knew that dry leave of stevia was sweeter than fresh one when extracted in boiling water over 20 minutes (dry leaves:water is 1:100). Then, this liquid consentrate must be stored in refrigerator over 18 hours to raise the sweetness. The best concentration for starfruit juice was 1% liquid concentrate which combined with 8% sucrose.